Peningkatan Kualitas Instagram Sekolah untuk Menambah Engagement di Akun Instagram SMA Cita Hati School Surabaya - Ekawati Purnomo; Budi Haryono; Januar Heryanto (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The presence of social media, especially Instagram, has become a crucial stage in efforts for promotion and engagement in educational institutions like SMA Cita Hati School Surabaya. The aim of this research is to investigate and enhance the quality of content posted on the school's Instagram account to achieve higher user engagement. The research method employed is an analysis with a qualitative approach. While content analysis has been conducted to understand trends and audience preferences, a participatory approach involves school stakeholders in designing strategies aligned with the values and goals of the educational institution. The research findings indicate that the Instagram account of SMA Cita Hati School Surabaya significantly enhanced interaction with its followers by improving the quality of visual and narrative content through well-planned engagement strategies. Based on information gathered and interviews with Instagram users, it was found that content focusing on school activities, student achievements, and special moments within the school community garnered more attention and engagement from followers. The practical impact of this research is to provide specific guidelines for school social media managers to optimize the use of Instagram as an effective communication tool. By understanding user preferences and implementing relevant strategies, schools can expand their communication reach, enhance their public image, and strengthen relationships within the school community. This study has shown positive results, the increase of the followers, engagements and reach numbers.